Statistical methods for the classification and risks for arterial hypertension - Cortez Gutiérrez, Hernán Óscar; Cortez Gutiérrez, Milton Milcíades; Durand Gonzales, César Ángel; Espinoza Flores, Braulio Pedro (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The objectives were to determine the factors associated with high blood pressure. To establish a relationship between the dependent variable hypertension and the independent variables Binary logistic regression taking hypertension as the dependent variable and the independent variables: cardiometabolic, sociocultural and sensory status. In conclusion, multiple linear and logistic regression established an association with age, diabetes, and anemia. The association between diabetes and hypertension has Chi-square Yates of 2.981 and a significance of 0.084< 0.10. The predictive confidence interval for systolic pressure of a person aged 83 years has been determined as: [105, 168].